Characteristics of sound localization in children with unilateral microtia and atresia and predictors of localization improvement when using a bone conduction device - Liu, Yujie; Zhao, Chunli; Yang, Lin; Chen, Peiwei; Yang, Jinsong; Wang, Danni; Ren, Ran; Li, Ying; Zhao, Shouqin; Gong, Shusheng (Frontiers in Neuroscience, 2022)
This study aimed to determine the characteristics of sound localisation in children with unilateral microtia and atresia (UMA) and the influence of a non-surgical bone conduction device (BCD). Hearing benefits were evaluated by the word recognition score (WRS), speech reception threshold, the international outcome inventory for hearing aids (IOI-HA), and the Speech, Spatial, and Qualities of Hearing Test for Parent (SSQ-P). Sound localisation was measured using broadband noise stimuli randomly played from seven loudspeakers at different stimulus levels (65, 70, and 75 dB sound pressure levels [SPLs]). The average unaided WRS and speech-to-noise ratio (SNR) for UMA patients was 18.27 ± 14.63 % and -5 ± 1.18 dB SPL, and the average aided WRS and SNR conspicuously changed to 85.45 ± 7.38 % and -7.73 ± 1.42 dB SPL, respectively. The mean IOI-HA score was 4.57 ± 0.73. Compared to the unaided condition, the mean SSQ-P score in each domain improved from 7.08 ± 2.5, 4.86 ± 2.27, and 6.59 ± 1.4 to 8.72 ± 0.95, 7.61 ± 1.52, and 8.55 ± 1.09, respectively. In the sound localisation test, some children with UMA were able to detect sound sources quite well and the sound localisation abilities did not deteriorate with the non-surgical BCD. Our study concludes that for children with UMA, the non-surgical BCD provided a definite benefit on speech recognition and high satisfaction without deteriorating their sound localisation abilities. It is an efficient and safe solution for the early hearing intervention of these patients.